Lack of motivation as suffering - Møller, Jane Ege (Tidsskrift for Forskning i Sygdom og Samfund, 2010)
This paper investigates how the concept of motivation functions in health promotion practice. It provides an analysis of the understandings and articulations of motivation at the levels of the state, health professionals, and citizens. It finds that motivation takes on different meanings and functions depending on the perspective; thus the general agreement on the importance of motivation in health promotion does not correspond to a mutual understanding of what motivation actually is: motivation works variously as technology, a statistically created collective informed consent, and a moral imperative. It is conceived of as an instrumentalized psychological entity but also expressed as a complex and context-bound phenomenon. The paper concludes by arguing that motivation must be seen as the latter: a relational concept, relating to concrete social and situational contexts rather than an instrumental psychological entity within the individual.